Biodegradable shape memory high-barrier transparent composite material, preparation method and application

By cross-linking reaction of PPC-P and other additives in a mixer, a biodegradable shape memory high-barrier transparent composite material was prepared, which solved the problem of difficulty in degrading traditional materials and insufficient shape memory performance, and achieved the preparation of materials with high barrier, excellent shape memory and good transparency.

CN119798953APending Publication Date: 2025-04-11安徽金普瑞新材料有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510027798.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional shape memory high barrier transparent heat-resistant composite materials are difficult to degrade, resulting in low reuse rate and environmental pollution. At the same time, a single amorphous polymer is difficult to obtain good shape memory effects and has poor toughness, which limits its application in food, electronic packaging and smart sensors.

Method used

By mixing PPC-P with PPC polyols, isocyanates, catalysts, lubricants, antioxidants and chain extenders in a certain proportion, and cross-linking reaction is carried out in a mixer to form a biodegradable shape memory high-barrier transparent composite material. This method improves shape memory performance and mechanical strength without affecting the excellent barrier performance of PPC-P.

Benefits of technology

It has realized the preparation of biodegradable shape memory high-barrier transparent composite materials, with excellent shape memory performance, barrier performance and transparency, and is suitable for food, electronic packaging and smart sensors and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005233261860000031
    Figure BDA0005233261860000031
  • Figure BDA0005233261860000041
    Figure BDA0005233261860000041
  • Figure BDA0005233261860000042
    Figure BDA0005233261860000042
Patent Text Reader

Abstract

The invention relates to the field of environment-friendly materials, in particular to a biodegradable shape-memory high-barrier transparent composite material, a preparation method and application. The biodegradable shape memory high-barrier transparent composite material is prepared from the following raw materials in parts by weight: 70 to 100 parts of PPC-P; 10 to 30 parts of PPC (Polypropylene Chloride) polyol; 0.1 to 1 part of hexamethylene diisocyanate (HD I); 0.01 to 0.1 part of a catalyst; 0.1 to 1.0 part of a lubricant; 0.1 to 0.5 part of an antioxidant; and 0.1-1 part of a chain extender. The preparation method comprises the following steps: adding the PPC-P, the antioxidant and the lubricant into an internal mixer for mixing, then sequentially adding the PPC polyol, the isocyanate and the catalyst into the internal mixer, and finally adding the chain extender for crosslinking to finally obtain the high-barrier transparent composite material with excellent shape memory performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmentally friendly materials, and in particular to a biodegradable shape memory high-barrier transparent composite material, a preparation method and an application thereof. Background Art

[0002] Shape memory high barrier transparent composite materials are mainly used in food, electronic packaging materials, construction, toys and sensor components, etc. However, traditional shape memory high barrier transparent heat-resistant composite materials are difficult to degrade under natural conditions, the product recycling rate is low, and a large amount of waste will cause serious environmental pollution problems. Therefore, we propose a biodegradable shape memory high barrier transparent composite material and a preparation method to solve this problem.

[0003] PPC-P is a terpolymer synthesized with phthalic anhydride, carbon dioxide and propylene oxide as comonomers. Compared with polypropylene carbonate (PPC), the water vapor and oxygen barrier effects of PPC-P are improved by 18 times and 4 times respectively, making it the first choice for barrier materials. However, PPC-P has an amorphous structure, and it is difficult for a single amorphous polymer to obtain a good shape memory effect by itself. The main reason is the irreversible deformation caused by chain slippage, and the weak entropy elasticity cannot provide sufficient recovery force. Secondly, PPC-P has poor toughness, and its elongation at break is ≤10%. These characteristics seriously limit the application of PPC-P in food, electronic packaging, smart sensors and other fields. PPC-TPU is a biodegradable material with excellent toughness prepared by the reaction of PPC diol with isocyanate and small molecule chain extender. Although it has excellent shape memory recovery rate, its shape memory fixation rate is low. Secondly, the oxygen and water vapor barrier effects of PPC-TPU are significantly lower than those of PPC-P, which seriously limits the application of PPC-TPU. However, the simple blend of PPC-P and PPC-TPU has poor compatibility between the two, which not only significantly reduces the barrier effect of the blend, but also significantly affects the transparency of the blend. In summary, it is still difficult to prepare a fully biodegradable composite material with excellent shape memory properties, excellent barrier properties and high transparency. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention proposes a biodegradable shape memory high-barrier transparent composite material, a preparation method and an application thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A biodegradable shape memory high barrier transparent composite material, wherein the raw materials for preparing the biodegradable shape memory high barrier transparent composite material include the following components in parts by weight:

[0007] PPC-P 70-100 copies;

[0008] PPC polyol 10-30 parts;

[0009] Hexamethylene diisocyanate 0.1-1 part;

[0010] Catalyst 0.01-0.1 part;

[0011] Lubricant 0.1-1.0 parts;

[0012] Antioxidant 0.1-0.5 parts;

[0013] Chain extender 0.1-1 part.

[0014] Furthermore, the PPC-P is a propylene phthalate-propylene carbonate copolymer synthesized using carbon dioxide as a main raw material.

[0015] Furthermore, the relative molecular mass of the PPC polyol is 2000±200, and the hydroxyl value is (55±5) mgKOH / g; the molar ratio of the isocyanate group to the hydroxyl group of the PPC polyol is (1.1-1.4):1.

[0016] Furthermore, the catalyst is one or more of phenolphthalein, imine and organic acid.

[0017] Furthermore, the lubricant is one or more of erucic acid amide, nano silicon dioxide and ethylene bisstearic acid amide.

[0018] Furthermore, the antioxidant is one or more of the antioxidant 1010 , the antioxidant 1076 , and the antioxidant 168 .

[0019] Furthermore, the chain extender is one or more of hexanediol, 1,4-butanediol and diethylene glycol.

[0020] A method for preparing a biodegradable shape memory high-barrier transparent composite material, the preparation method comprising the following steps: firstly adding PPC-P, an antioxidant and a lubricant into an internal mixer for mixing, then adding PPC polyol, isocyanate and a catalyst into the internal mixer in sequence, and finally adding a chain extender for cross-linking, thereby finally obtaining a high-barrier transparent composite material with excellent shape memory performance.

[0021] Furthermore, the temperature of the internal mixer is set to 80-190° C., and the mixing speed is 30-150 rpm.

[0022] The above-mentioned biodegradable shape memory high barrier transparent composite material is applied in the fields of food, electronic packaging and smart sensors.

[0023] Beneficial effects of the present invention:

[0024] 1. During the melt blending process of PPC polyol and PPC-P, PPC polyol and isocyanate react to form PPC-TPU toughening phase. Combined with the use of chain extender, it not only greatly improves the shape memory performance of PPC-P, but also gives it good mechanical strength and toughness without affecting the excellent barrier properties of PPC-P.

[0025] 2. The PPC-TPU toughening phase formed by in-situ polymerization on PPC-P of the present invention does not affect the excellent transparency of PPC-P. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The glass transition temperature (Tg) of PPC-P is 46 °C, Shandong Lianchuang Co., Ltd.;

[0028] The relative molecular mass of PPC polyol is 2000±200, the hydroxyl value is (55±5) mgKOH / g, and it is from Jiangsu Zhongke Jinlong Chemical.

[0029] Isocyanate was hexamethylene diisocyanate (HDI), Wanhua Chemical Group Co., Ltd.

[0030] The chain extender is one or more of 1,4-butanediol (BDO), diethylene glycol (DEG), and 1,4-cyclohexanedimethanol (CHDM).

[0031] The catalyst is one or more of phenolphthalein, imine and organic acid.

[0032] The lubricant is ethylene bis stearamide EBS, Changzhou Kesai Chenggong Plastic Material Co., Ltd.

[0033] The antioxidant was antioxidant 1010, Liangshan Xinxiang New Materials Co., Ltd.

[0034] In each embodiment and comparative example, the main raw materials come from the following sources:

[0035] Table 1 Raw materials and sources

[0036]

[0037]

[0038] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0039] Table 2: Raw materials and dosage (g) in Examples 1-5 and Comparative Examples 1-3

[0040]

[0041] Example 1

[0042] The formula components in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to, and the preparation was carried out according to the following method: first, PPC-P, antioxidant and lubricant were added to the internal mixer and mixed, and then PPC polyol, isocyanate and catalyst were added to the internal mixer in sequence, and the composite material was obtained when the reaction reached a certain viscosity. The temperature of the internal mixer was 150°C and the speed was 30 rpm.

[0043] Example 2

[0044] The formula components in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to, and the preparation was carried out according to the following method: first, PPC-P, antioxidant and lubricant were added to the internal mixer and mixed, and then PPC polyol, isocyanate and catalyst were added to the internal mixer in sequence, and the composite material was obtained after the reaction reached a certain viscosity. The temperature of the internal mixer was 160°C and the speed was 50 rpm.

[0045] Example 3

[0046] The formula components in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to, and the preparation was carried out according to the following method: first, PPC-P, antioxidant and lubricant were added to the internal mixer and mixed, and then PPC polyol, isocyanate and catalyst were added to the internal mixer in the order of sequence, and the composite material was obtained after the reaction reached a certain viscosity. The temperature of the internal mixer was 150°C and the speed was 80 rpm.

[0047] Example 4

[0048] The formula components in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to, and the preparation was carried out according to the following method: first, PPC-P, antioxidant and lubricant were added to the internal mixer and mixed, and then PPC polyol, isocyanate and catalyst were added to the internal mixer in sequence, and after the reaction reached a certain viscosity, a chain extender was added for cross-linking, and finally a composite material was obtained. The temperature of the internal mixer was 160°C and the speed was 100 rpm.

[0049] Example 5

[0050] The formula components in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to, and the preparation was carried out according to the following method: first, PPC-P, antioxidant and lubricant were added to the internal mixer for mixing, and then PPC polyol, isocyanate and catalyst were added to the internal mixer in the order of sequence, and after the reaction reached a certain viscosity, a chain extender was added for cross-linking, and finally a composite material was obtained. The temperature of the internal mixer was 150°C and the speed was 50 rpm.

[0051] Comparative Example 1

[0052] The formulation components in Table 2 were used as raw materials, and the raw material amounts in Table 2 were referred to for preparation according to the following method: first, the temperature of the internal mixer was set to 160° C. and the speed was 50 rpm, and PPC-P, antioxidant and lubricant were added to the internal mixer for mixing.

[0053] Comparative Example 2

[0054] The ingredients in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to for preparation according to the following method:

[0055] (1) Synthesis of PPC-TPU

[0056] First, set the temperature of the internal mixer to 120°C and the speed to 50 rpm, add PPC polyol, antioxidant and lubricant into the internal mixer and mix them first, then add isocyanate and catalyst into the internal mixer in sequence, after the reaction reaches a certain viscosity, set the temperature of the internal mixer to 170°C and the speed to 80 rpm, then add chain extender for cross-linking, and finally obtain PPC-TPU.

[0057] (2) Physical blending of PPC-P and PPC-TPU

[0058] The PPC-TPU, PPC-P, antioxidant and lubricant synthesized in (1) are added to an internal mixer and mixed, and a composite material is obtained after the mixing is uniform. The temperature of the internal mixer is 180° C. and the speed is 100 rpm.

[0059] Comparative Example 3

[0060] The formula components in Table 2 were used as raw materials, and the raw material dosages in Table 2 were referred to, and the preparation was carried out according to the following method: first, PPC-P, antioxidant and lubricant were added to an internal mixer and mixed, and then PPC polyol was added to the internal mixer, and the composite material was obtained after the viscosity reached a stable state. The temperature of the internal mixer was 160°C and the speed was 100 rpm.

[0061] Composite material barrier performance test: oxygen transmission rate is tested according to ISO15105; water vapor transmission rate is tested according to ISO2528.

[0062] Composite material transmittance and haze test: Test the transmittance and haze of the composite film in accordance with GB / T2410-2008.

[0063] Composite material shape memory performance test: Cut the composite material sheet into 10mm (length) × 4mm (width) × 1mm (thickness) strips, and use a thermomechanical analyzer (TMA Q400) in the tensile mode to test the shape memory performance of the composite material. According to the thermomechanical test results, the following formulas 1-(1) and 1-(2) can be used to obtain two main parameters for quantitatively characterizing the shape memory performance of the sample: shape fixation rate (Rf) and shape recovery rate (Rr) are the temporary shape memory ability and permanent shape recovery ability, respectively. The test temperature range is 0℃-70℃.

[0064]

[0065] In equations 1-(1) and 1-(2), εun l oad is the strain of the sample after stress is removed, εi n ital is the initial strain after thermal history is removed, εload is the maximum strain of the sample after stress is applied, and εrec is the strain after the sample is reheated and recovers its shape.

[0066] Table 3 Performance test results of products of Examples 1-3 and Comparative Examples 1-3

[0067]

[0068] It can be seen from Comparative Examples 1-3 and Examples 1-5 that compared with the composite materials prepared by direct blending of PPC-P and PPC-TPU, the PPC-P / PPC-TPU composite materials prepared by in-situ polymerization have higher shape fixation rate and shape recovery rate (>97%), excellent barrier properties and high transparency, showing broad application prospects of fully biodegradable composite materials in the fields of food, electronic packaging, and smart sensors.

[0069] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A biodegradable shape memory high barrier transparent composite material, characterized in that: The raw materials for preparing the biodegradable shape memory high barrier transparent composite material include the following components by weight: PPC-P 70-100 copies; PPC polyol 10-30 parts; Hexamethylene diisocyanate 0.1-1 part; Catalyst 0.01-0.1 part; Lubricant 0.1-1.0 parts; Antioxidant 0.1-0.5 parts; Chain extender 0.1-1 part.

2. The biodegradable shape memory high barrier transparent composite material according to claim 1, characterized in that: The PPC-P is a propylene phthalate-propylene carbonate copolymer synthesized using carbon dioxide as a main raw material.

3. The biodegradable shape memory high barrier transparent composite material according to claim 1, characterized in that: The relative molecular mass of the PPC polyol is 2000±200, and the hydroxyl value is (55±5) mgKOH / g; the molar ratio of the isocyanate group to the hydroxyl group of the PPC polyol is (1.1-1.4):

1.

4. The biodegradable shape memory high barrier transparent composite material according to claim 1, characterized in that: The catalyst is one or more of phenolphthalein, imine and organic acid.

5. The biodegradable shape memory high barrier transparent composite material according to claim 1, characterized in that: The lubricant is one or more of erucic acid amide, nano silicon dioxide and ethylene bis stearic acid amide.

6. The biodegradable shape memory high barrier transparent composite material according to claim 1, characterized in that: The antioxidant is one or more of the antioxidant 1010 , the antioxidant 1076 , and the antioxidant 168 .

7. The biodegradable shape memory high barrier transparent composite material according to claim 1, characterized in that: The chain extender is one or more of hexanediol, 1,4-butanediol and diethylene glycol.

8. A method for preparing a biodegradable shape memory high barrier transparent composite material, characterized in that: The preparation method comprises the following steps: according to the material ratio in claim 1, PPC-P, antioxidant and lubricant are first added into an internal mixer for mixing, then PPC polyol, isocyanate and catalyst are added into the internal mixer in sequence, and finally a chain extender is added for cross-linking, so as to finally obtain a high-barrier transparent composite material with excellent shape memory performance.

9. The method for preparing a biodegradable shape memory high barrier transparent composite material according to claim 8, characterized in that: The temperature of the internal mixer is set at 80-190° C., and the mixing speed is 30-150 rpm.

10. Application of a biodegradable shape memory high barrier transparent composite material as claimed in any one of claims 1 to 7 in the fields of food, electronic packaging and smart sensors.

Citation Information

Cited By

  • Completely biodegradable resin as well as preparation method and application thereof

    CN120383814A

  • A fully biodegradable resin, its preparation method and application

    CN120383814B